2004
DOI: 10.1023/b:nere.0000018853.30131.4d
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Produced During Ischemia Is Toxic but Crucial to Preconditioning-Induced Ischemic Tolerance of Neurons in Culture

Abstract: The present study investigated the roles of nitric oxide (NO) in preconditioning (PC)-induced neuronal ischemic tolerance in cortical cultures. Ischemia in vitro was simulated by subjecting cultures to both oxygen and glucose deprivation (OGD). A sublethal OGD (PC) significantly increased the survival rate of neurons when cultures were exposed to a lethal OGD 24 hr later. Both the inhibition of nitric oxide synthase (NOS) and scavenging of NO during PC significantly attenuated the PC-induced neuronal tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
(23 reference statements)
0
28
0
Order By: Relevance
“…In addition, we also demonstrated the possibility that nitric oxide (NO) produced during PC is involved in the development of the PC-induced ischemic tolerance of neurons (10). Therefore, we first investigated whether the PC-induced suppression of the rise in the concentration of extracellular Glu was antagonized by the inhibition of NO production during PC in neuron/astrocyte co-cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, we also demonstrated the possibility that nitric oxide (NO) produced during PC is involved in the development of the PC-induced ischemic tolerance of neurons (10). Therefore, we first investigated whether the PC-induced suppression of the rise in the concentration of extracellular Glu was antagonized by the inhibition of NO production during PC in neuron/astrocyte co-cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Yun et al (24) have recently demonstrated that the activation of p21 RAS induced by NO derived from nNOS is responsible for the PC-induced tolerance of neurons, suggesting that NO is a key mediator in the process leading to resistance against lethal ischemia. We have previously demonstrated that the enhanced production of NO is crucial to the development of PC-induced ischemic tolerance of neurons in neuron/astrocyte co-cultures (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuron/astrocyte co-culture Culture methods were described previously in detail (11)(12)(13). In brief, neurons/astrocytes were prepared from 17-day-old embryonic rat cortices and grown in Dulbecco's modified Eagle's medium (DMEM, Gibco, Grand Island, NY) which was supplemented with 10% heat-inactivated fetal bovine serum (FBS), 10% Ham's F12, and 0.24% penicillin/streptomycin (culture medium) and maintained in a 5% CO 2 incubator at 37 °C.…”
Section: Methodsmentioning
confidence: 99%